AN ANALYSIS OF DEIXIS IN SONG LYRIC MAROON 5 MEMORIES, THIS LOVE, ANIMALS - Neneng Shinta Rachmawati; Iman Santoso (PROJECT (Professional Journal of English Education), 2023)
Depending on the context, the languages deixis expression is used to indicate who, where, and when. The aims of the studies is to know the type of deixis used in Maroon 5 song lyrics. The method used by the researcher is qualitative. This song was picked by the researcher because it is popular among many people, particularly teens, and is simple to listen to. There are three steps in the data collection process: first, data reduction; second, data display; and third, data verification. Personal, spatial, and temporal deixis are all investigated in this study. The researcher identified 71.42% data in personal deixis, followed by 15.23% data in spatial deixis and 13.35% data in temporal as a consequence of this research.